Exploring the supply chain management of fair trade business: case study of a fair trade craft company in China - Kaifeng Zhang; Zheng Liu; Ping Wang (Cogent Business & Management, 2020)
For two decades, fair trade has served as an alternative approach of trading that encourages minimal returns, sustainability, and ethics, by offering producers in developing countries better trading conditions and secured rights. This movement has emerged recently in China, with companies involving domestic trading between richer and poorer regions. However, lack of third-party certification, standardization, process control, public awareness, and brand recognition continue to be challenges. To understand the current fair trade business in China, this paper investigates important decision-making areas from a supply chain management perspective. With the nature of empirical studies, an in-depth case analysis of a fair trade craft company has been conducted along with the purchasing and supplier relationship management, internal operations, and marketing and customer relationship management. This company currently combines the role of fair trade organization and retailer, by implementing an in-house certification system and vertically integrating the supply chain. Findings also highlight risk at each stage of supply chain. Compared with the western society, the unique features of Chinese fair trade business are captured with prioritized areas for improvement. This research contributes to the fair trade literature by providing exploratory study into emerging issues in the supply chain, particularly inside developing countries. The recommendations also create value for policy-makers and practitioners of fair trade companies.
Keywords: 650; Fair trade; social enterprise; supply chain management; China